2019
DOI: 10.3389/fpsyg.2019.01349
|View full text |Cite
|
Sign up to set email alerts
|

Participants Over-Estimate How Helpful They Are in a Two-Player Game Scenario Toward an Artificial Confederate That Discloses a Diagnosis of Autism

Abstract: Research on how autistic people are perceived by neurotypical people indicates that disclosing a diagnosis leads to a positive discriminatory bias; however, autobiographical autistic accounts indicate that diagnostic disclosure often results in negative discriminatory behavior. We report on an exploratory study to compare people’s self-reported helping behavior with their actual helping behavior toward an assumed autistic collaborator. We led 255 participants to believe that they were interacting online with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…These biases against autistic individuals are formed quickly by non-autistic people, and do not change with increased exposure (Sasson et al, 2017). Non-autistic people overestimate how egocentric autistic family members are (Heasman and Gillespie, 2018), while also overestimating the helpfulness of their own behaviors toward autistic people (Heasman and Gillespie, 2019b). Taken together, this body of research provides evidence that autistic social difficulties may be in part due to the perceptions of, and judgments made by, non-autistic people.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…These biases against autistic individuals are formed quickly by non-autistic people, and do not change with increased exposure (Sasson et al, 2017). Non-autistic people overestimate how egocentric autistic family members are (Heasman and Gillespie, 2018), while also overestimating the helpfulness of their own behaviors toward autistic people (Heasman and Gillespie, 2019b). Taken together, this body of research provides evidence that autistic social difficulties may be in part due to the perceptions of, and judgments made by, non-autistic people.…”
Section: Introductionmentioning
confidence: 73%
“…Autistic people may feel more comfortable with other autistic people (Crompton et al, 2020a), and non-autistic people may feel more comfortable with other non-autistic people (Cage and Burton, 2019;DeBrabander et al, 2019) and this may be enhanced by being aware of the diagnostic status of the other person in the interaction. Being aware of the diagnostic status of the person with whom they were interacting may have changed participants' behavior, however, previous research has shown that when non-autistic people know that they are interacting with an autistic person, they attempt to behave in a helpful way (Heasman and Gillespie, 2019b), and sharing diagnostic information results in greater acceptance of autistic people (Sasson and Morrison, 2019). As such, it may be hypothesized that there may be an even larger effect on rapport between mixed and single neurotype pairs if participants were blind to the diagnostic status of their partner.…”
Section: Discussionmentioning
confidence: 99%
“…Second, participants were aware of the diagnostic status of the person with whom they were interacting, which could have affected their behaviour. However, previous research has shown that when non-autistic people believe they are interacting with an autistic person, they attempt to behave in a helpful way ( Heasman & Gillespie, 2019b ), and sharing diagnostic information results in greater acceptance of autistic people ( Sasson & Morrison, 2017 ). As such, it may be hypothesised that an even larger effect would be found if participants were blind to the diagnostic status of the others in their diffusion chain.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with the double-empathy theory of autism which suggests that autistic and non-autistic people have a mutual difficulty in understanding and empathising with one another due to differences in how each person understands and experiences the world, rather than because of a communicative deficit on the part of the autistic person ( Milton, 2012 ). Neurotypical people have been shown to overestimate how ego-centric their autistic family members are ( Heasman & Gillespie, 2018 ), and overestimate how helpful they are to autistic people ( Heasman & Gillespie, 2019 ). Our findings suggest that this translates into real-world difficulties in interactions with neurotypical friends and family that may affect the mental health, well-being and self-esteem of autistic people.…”
Section: Discussionmentioning
confidence: 99%